Biomonitoramento da qualidade da água e percepção ambiental na bacia hidrográfica Apodi-Mossoró, RN - Silva, Ana Paula Cardoso (2013)
Water scarcity is a reality for the inhabitants of the Brazilian semiarid region. The problem, in quantitative terms , is caused due to local climatic conditions due mostly to a water deficit. Qualitatively, results of multiple uses and resulting contamination by human activities. Eutrophication is presented as a threat to the sustainable use of water resources, in order to favor the predominance of dense populations of cyanobacteria, which can be potentially harmful to human health. The aim of this study is to understand the population dynamics of phytoplankton and cyanobacteria to assess water quality of reservoirs Santa Cruz do Apodi and Pau dos Ferros belonging to bacia Apodi Mossoró-RN . Water samples were collected monthly between October 2011 and May 2012 in reservoirs Santa Cruz do Apodi and Pau dos Ferros, in this latter , in Jan/12 we performed a diel profile . The abiotic variables obtained in the field and in the laboratory were: water temperature , dissolved oxygen , pH , turbidity , transparency , total nitrogen and total phosphorus . Phytoplankton samples were collected with a plankton net and bottle of Van dorn . Were performed : identification , quantification , calculation of biovolume , classification into functional groups and index calculation phytoplankton assembly ( Q ) , cyanotoxins were quantified by ELISA . Statistical analyzes supported the evaluation of the dynamics between biotic and abiotic factors. A questionnaire was conducted to examine the conceptions of the population, education professionals and students. The reservoir of Pau dos Ferros, shallow , turbid and eutrophic showed dominance of the functional group SN throughout the sample period . The phytoplankton biomass ranged from 20 to 70 mm ³ . L - 1, the lowest values coincided with the increase of the mixing zone and transparency, which contributed to the occurrence of a change in species composition phytoplankton . The application of the index Q proved relevant, the reservoir of Pau dos Ferros , depending on the species present , was classified ecologically as bad for almost the entire sample period . The reservoir Santa Cruz do Apodi showed low biomass ( 0.04 and 4.31 mm ³ . L - 1 ) and greater diversity in the phytoplankton composition . According to the index assembly (Q ), it showed moderate condition during most of the period influenced by different functional groups of typical meso- eutrophic environment (K S0, H1, C, F , J , E, D and N) . Associations of diatoms and green algae D and X1 succeeded populations of cyanobacteria in periods marked by greater instability in the system , caused by wind or rain. In summary , the occurrence of drought has a direct influence on the hydrological conditions of the reservoirs , in general, these events, reducing the reservoir level is directly related to decreased water quality and increased density of phytoplankton occurring predominance of cyanobacteria , the index Q reflected well to changes in phytoplankton composition , being a good indicator for biomonitoring of reservoirs in this study and survey of previous conceptions showed the need to work on environmental awareness for the preservation of water resources by conducting workshops for Environmental Education